Developing Students' Digital Literacy with Character Education Content toward the Era of Society 5.0 - Naniek Jusnita; Silvani Umar Ali; Susana Bahara; Hani Hani; Iga Mawarni (FKIP Universitas Khairun, 2026)
This study aims to determine and identify students' digital literacy skills and proficiency, as well as how to integrate character education and digital literacy in order to prepare students to face the demands and challenges of the digital world. This study involved one eighth-grade class at SMP Negeri 1 Kota Ternate with 20 students. The methods used were classroom observation, interviews with teachers, students, and parents, as well as analysis of the character education content in the curriculum. The results of the study show that students are able to utilize media, tools, methods, and learning strategies based on digital technology, such as in focus, computers, online learning applications, online educational games, and classroom chat in Civics, Science, and English subjects, which have provided an interesting, enjoyable, challenging, enthusiastic, critical, insightful, and character-building learning experience for students. Through each learning theme, teachers integrated character education, such as the theme “Behavior Supporting Archipelago Insight” (Civics education) in the form of tolerance and mutual respect, fostering love for the country and nation, obeying applicable regulations, developing tolerance, mutual respect, and rejecting the spread of hatred, and expressing opinions through appropriate channels. In the theme of “Vibrations” (science learning), the integrated character education is precision, cooperation, responsibility, and the ability to make good decisions in group discussions, practicums, and observations. And in the theme of “My Favorite Food” (English lessons), the character education that appear is an attitude of gratitude (religious), discipline, responsibility, communication skills, self-confidence, tolerance, and respect for differences.